"Natural integration": A new approach to integration policy in developing countries - Rasul Shams (Hamburg Institute of International Economics (HWWA), 1998)
The article is based on the idea that geographic proximity is an essential factor for international integration policies due to its impact on the intensity of bilateral foreign trade and growth rate. Development is analysed as a process of structural diversification, whereby the country in question runs through different stages encountering co-ordination problems at the structural change-over points. Natural integration of neighbouring countries around a pivot country is shown to be an alternative to protectionist and multilateral liberalisation policies fostering structural diversification and overcoming coordination problems.
Keywords: 330; Handelsregionalisierung; Außenhandelsliberalisierung; Entwicklung; Strukturwandel; Entwicklungsländer